Trace metal bioaccumulation in Israeli Mediterranean coastal marine mollusks. (10th December 2015) - Shefer, Edna; Silverman, Jacob; Herut, Barak
Abstract: During the period 1995–2012, trace metal levels were monitored on an annual basis in marine mollusks ( Donax trunculus, Mactra stultorum, Patella sp. and Cellana rota ) along the Mediterranean coast of Israel in polluted and unpolluted areas. In general, these records show that: 1) Mercury and cadmium concentrations declined precipitously in Haifa Bay specimens in response to pollution load reductions; 2) Nonetheless, Haifa Bay specimens still show higher trace metal concentrations compared to specimens from other sites along the Israeli shore; 3) Hot spots of pollution were identified along the Haifa Bay shore, demonstrating the sensitivity of these specimens to events of contaminated sediments re-suspension. These events were likely caused by winter flooding in Qishon and Na'aman rivers and dredging operations in Haifa Port; 4) Trace metal concentrations in Patella sampled north of Haifa Bay are higher than those measured in specimens sampled south of Haifa Bay, suggesting that the impact range is greater than previously considered and pollution loading in Haifa Bay could be projected northward via general transport processes; 5) Cadmium levels in Patella sampled along the coast displayed an increasing trend over time that could hypothetically be associated with ocean acidification and warming trends; 6) Excess of wet weight to shell length ratio in Patella specimens from Haifa Bay that exhibited higher trace metal accumulation, was lower than expected, possibly because of environmental stress, e.g. the energetic cost of detoxification. These findings provide supporting evidence for the importance and utility of trace metal bioaccumulation monitoring and sediment rehabilitation in polluted estuaries and other coastal regions as well as providing a basis for closer regulation and inspection of dredging operations.